Réflexions sur le décloisonnement des Institutions financières - Labrecque, Jacques (Assurances)

(untitled) (HEC Montréal, 1987)
The extent of deregulation and its implications are still difficult to predict. In the following article, Mr. Jacques Labrecque examines the situation from a property and casualty insurer's perspective and the opinions expressed are solely his own. The facts presented are of special interest to those who see deregulation as more than a passing phenomenon or a change happening.